President's Speech for 2nd Malaysia Debate Open - Prof. Dr. Zaharin Yusoff, (Multimedia University, 2010)
This was the welcoming speech addressed by MMU President, Prof. Dr. Zaharin bin Yusoff during 2nd Malaysia Debate Open.